Challenges between academic life and breastfeeding: A systematic review (Research, Society and Development, 2021)
This study aimed to conduct a search for articles published between 2015 and 2020, which had as an approach to analyze the actions promoted by higher education institutions in support of student mothers in reconciling academic demands and breastfeeding. 15 studies were selected. which were relevant to the topic addressed, being only one of these in Brazil, which demonstrates the need for more studies related to the public of nursing mothers at university. The results presented in the selected articles demonstrate gaps in the support offered by higher education institutions to university mothers, such as the absence of adequate places for breastfeeding and breast milking, inflexible academic activities schedules, making it difficult to reconcile breastfeeding with curricular activities, little reception from classmates and teachers, in addition to sociocultural issues that hinder the academic trajectory of student mothers. In this sense, the study promotes reflection on the theme, with the aim of encouraging Brazilian researchers, in view of the scarcity of Brazilian scientific productions that have a look focused on this group of women inserted in universities. Furthermore, it is important to emphasize the movement of universities promoting health, which has as its principle the participation of the university in the health promotion process, as it presents a rich space for the development of learning environments and healthy experiences for the academic community.